Nonlinear Adjustment, Purchasing Power Parity and the Role of Nominal Exchange Rates and Prices - Joscha Beckmann (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2011)
Although the literature on purchasing power parity (PPP) is rich in controversy, the relative contribution of prices and nominal exchange rates to real exchange rate movements which restore PPP disequilibria has rarely been put under any close scrutiny. Using monthly data from 1973:01 to 2009:12 from the USA, UK, Germany, France and Japan, this paper as a first step applies a cointegrated VAR framework to test for stationary real exchange rates and linear adjustments in prices and nominal exchange rates. As a second step, ESTR error correction models are fitted to test whether nonlinear error correctional behaviour characterizes the data. The results clearly indicate that the nominal exchange rate is responsible for the nonlinear mean reverting behaviour in real exchange rates and also mainly drives overall adjustment. Applying dynamic stochastic simulations based on the estimated models, this study also confirms recent results that the half-life times of real exchange rate shocks are significantly smaller than the consensus benchmark of three to five years.
Keywords: E44; F31; G15; 330; Purchasing power parity; cointegration; nonlinear vector error correction